Bob Marley spiritual journey (United Kingdom : WHE International Limited)
Bob Marley grew up influenced by the Rude Boy culture in the ghettos of Kingston, but during his relatively short life Bob Marley achieved almost Saint like status through his music and his spiritual message of one love and world peace. In this 55 minute programme, featuring his music, film footage shown for the first tie and exclusive interviews, we seek to examine the motivations of the man, to provide an in-sight into his relationships and the development of his musical excellence through the people that knew and worked with him.
Fifty-five (55) minutes.
Keywords: Bob Marley, 1945-1981.